The Effect of Ownership, Expense Ratio, Capital Ratio and Liquidity on Financial Performance Commercial Banks (Study on Issuers on IDX) - Andarwati Andarwati (Journal of International Conference Proceedings, 2022)
ABSTRACTThe  purpose  of  this  study is  to  analyze  the  influence  between  Ownership,  Expense Ratio, Capital Ratio and Liquidity On Financial Performance of Commercial Banks. Method. The technique used for sampling in this study was purposive sampling, with a total sample of 15 companies.The analytical method used to answer research problems and test hypotheses is a multiple regression analysis technique using SPPS. The results of this study show 1) bank ownership, the assets to loan ratio has a significant positive effect on the performance of  public  banks,  2)  the  cost  of  funds,  deposit  risk  ratio,  banking  ratio  has  a  significant negative effect on the performance of commercial banks, 3) the acid test ratio has no effect on performance of commercial banks. Keywords: Capital Ratio, Expense Ratio, Financial Performance, Liquidity, Ownership.